Ensuring continuity of care during the COVID-19 pandemic in Guinea: Process evaluation of a health indigent fund - Lansana Barry; Lansana Barry; Mariama Kouyaté; Abdoulaye Sow; Willem Van De Put; John De Maesschalck; Bienvenu Salim Camara; Norohaingo Adrianaivo; Alexandre Delamou; Alexandre Delamou (Frontiers Media S.A., 2022)
BackgroundThe emergence of the COVID-19 has disrupted the health and socioeconomic sectors, particularly in resource-poor settings such as Guinea. Like many sub-Saharan countries, Guinea is facing shortcomings related to its fragile health system and is further affected by the passage of the Ebola virus disease. The pandemic has worsened the socio-economic situation of the poorest people, leading to their exclusion from health care. To promote access to care for the most vulnerable populations, a system was set up to provide care for these people who are victims of health marginalization to promote their access to care. This study aimed to analyze access to health services by vulnerable populations during the COVID-19 pandemic in Guinea through the establishment of a health indigent fund (HIF).MethodsThis was a qualitative study to assess the project implementation process. A total of 73 in-depth individual interviews were conducted with beneficiaries, health workers, community health workers and members of the HIF management committee, and a few informal observations and conversions were also conducted in the project intervention areas. The data collected were transcribed and coded using the deductive and inductive approaches with the Nvivo software before applying the thematic analysis.ResultsA total of 1,987 indigents were identified, of which 1,005 were cared for and 64 referred to all 38 intervention health facilities within the framework of the HIF. All participants appreciated the project's social action to promote access to equitable and quality health care for this population excluded from health care services. In addition, the project has generated waves of compassion and solidarity toward these "destitute" people whose main barrier to accessing health care remains extreme poverty. A state of poverty that leads some to sell their assets (food or animal reserves) or to go into debt to ensure access to care for their children, considered the most at risk.ConclusionThe HIF can be seen as an honest attempt to provide better access to health care for the most vulnerable groups. Some challenges need to be addressed including the current system of acquiring funds before the attempt can be considered scalable.